PROUNI: política pública de acesso ao ensino superior – um estudo sobre a possibilidade de atenuação das desigualdades sociais com os egressos de uma instituição de educação superior privada de Brasília. - Silva, Thiago Aparecido Gomes da (Universidade do Vale do Rio dos Sinos, 2018)
This dissertation focuses on the expansion of higher education in Brazil in the last decades. It will focus its analysis on the actions of the University Program for All - ProUni, regarding the process of insertion and social inclusion of students through the granting of scholarships to study undergraduate studies in private institutions of higher education. In this study, I relate discussions about inequalities, public policies and access to higher education to question the extent to which social inequalities have been attenuated by the expansion of higher education and by the access of social sectors that previously had no opportunities to reach this level of education through more equitable educational policies. A general contextualization of the expansion of higher education in Brazil was made, through data from the last Brazilian Census of Higher Education, to place ProUni within the policies of equity in the area of education. This will focus, in particular, the institution LS Faculdade de Brasília and the developments that ProUni has brought in the institutional level and in relation to the beneficiary subjects of the program that were formed in this Institution of higher education. The research was a mixed (qualitative-quantitative) approach, performed through documentary research and questionnaire application to colleagues from ProUni studies, considering their social trajectory. It was complemented with the systematization of secondary data, whose sources were the Brazilian Census of Higher Education and data referring to ProUni in the institution under investigation. As main results, it is pointed out that, in the research institution, there are signs of attenuation of the inequalities. Examples were the racial dimension, with students from the last five years presenting equal percentages between the self-declared white population and the black population; the increase of the years of schooling in relation to the parents, being the beneficiary of ProUni the first student of the family; and that of women with children, more qualified professional integration and higher salary expectations.
Keywords: ProUni; Educação Superior; Políticas Públicas; Equidade; ProUni; Higher Education; Public Policies; Equity; ACCNPQ::Ciências Humanas::Sociologia